Neutral cysteine protease of Spirometra mansoni plerocercoid invoking an IgE response - Kong, Y; Kang, SY; Kim, SH; Chung, YB; Cho, SY (CAMBRIDGE UNIV PRESS, 1997)
When crude extracts of Spirometra mansoni plerocercoid (sparganum) were analysed by SDS-polyacrylamide gel electrophoresis (PAGE)/immunoblot using patients' sera, IgE antibodies reacted specifically with 21, 27 and 53 kDa proteins. The 21 and 27 kDa proteins have been previously characterized as cysteine proteases. In this study, the 53 kDa protein was confirmed, by immunoprecipitation, to induce a specific IgE response. The protein was purified by affinity chromatography using an IgG1 (kappa 2) type mAb. The protein was partially sensitive to peptide-N-4-(N-acetyl-beta-glucosaminyl)asparagine amidase F (endo F) digestion. It exhibited an endoproteinase activity in a thiol-dependent manner preferentially degrading benzoyloxycarboxyl-phenplalanyl-arginyl-4-methoxy-beta-naphthylamide (Z-phe-arg-MNA) of a panel of substrates tested. This endoprotease activity was maximal at pH 6 . 5 and in 0 . 1 M sodium phosphate. The proteolytic activity was inhibited by 10(-5) M L-trans-epoxysuccinyl-L-leucylamido-(4-guanidino)butane (E-64) and 1 mM iodoacetamide (IAA), and potentiated by dithiothreitol (DTT, 5 mM).
Keywords: DUST MITE ALLERGEN; SCHISTOSOMA-MANSONI; TRYPANOSOMA-CRUZI; SEQUENCE-ANALYSIS; PROTEINASE; PURIFICATION; SPARGANOSIS; RECEPTOR